Methodist narratives, religious justification and the American occupation of the Philippines, 1899-1904 (UP Los Baños Journal, 2022)
Just as the Roman Catholic Church played an important role during the Spanish colonization of the Philippines, the Protestant Church also made its mark during the United States of American imperialistic agenda in the country. One of the things where they participated with was the creation of the narratives to justify American imperialism and consequently the need of Protestantism in the Philippines. This paper examined these narratives and symbolism from primary sources specifically those published or written mainly by members of the Methodist Episcopal Church during the late 1890s to the early 1900s. This paper also considered how the Methodist writers depicted the spiritual needs of the country not only of Filipino but also the Americans thus creating further justification for American presence and Protestant missions. Lastly, the paper also identified several of the strategies that the Methodist Church employed for their early missions in the country which reflects their justification. The paper recognizes the power of narratives, such as Biblically inspired representations of the U.S., in justifying conquests as well as the remembering or forgetting of such act. And for this recognition that the paper aims to add to the literatures reevaluating the narratives surrounding the Philippine-American War, American imperialism, and Protestantism in the country among others.